2019
DOI: 10.18203/2349-2902.isj20191895
|View full text |Cite
|
Sign up to set email alerts
|

The non traumatic acute abdomen and its clinical spectrum

Abstract: Background: Acute abdomen poses a big challenge to the general surgeons in terms of both diagnosis and management. The aim of this study was to know in detail the clinical and postoperative outcome in non traumatic acute abdomen.Methods: Prospectively collected data of 326 patients with non traumatic acute abdomen admitted in PES institute of medical sciences and research, Kuppam from November 2016 to June 2018. All patients were subjected to clinical examination, relevant blood and imaging investigations, Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
3
1
0
Order By: Relevance
“…Patients who had a record of body temperatures over 37.5 had significant association with unfavourable treatment outcome. This finding is similar with a study conducted at Tikur Anbessa Hospital, 25 which revealed that patients with records of high body temperatures had a lower chance of improving than those with normal body temperatures. This might be due to fever being characterized by a temperature of 37.5°C or higher and is accompanied by alterations in the immunological and metabolic systems.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Patients who had a record of body temperatures over 37.5 had significant association with unfavourable treatment outcome. This finding is similar with a study conducted at Tikur Anbessa Hospital, 25 which revealed that patients with records of high body temperatures had a lower chance of improving than those with normal body temperatures. This might be due to fever being characterized by a temperature of 37.5°C or higher and is accompanied by alterations in the immunological and metabolic systems.…”
Section: Discussionsupporting
confidence: 90%
“…14 Participants who had guarding on physical examination had significant association with unfavourable treatment outcome. Similar findings were observed at Black Lion Hospital, 25 and Goba Hospital. 26 This is owing to the patient's aversion to have their abdomen handled due to peritoneal inflammation and irritation, a condition known as guarding.…”
Section: Discussionsupporting
confidence: 86%
“…The age range of this study as indicated in Table 1 is in agreement with the findings of the studies conducted by Lin and Lin 2013;Arredondo (2018) and Aviral et al (2005). However, this was contrary to the study conducted by Kumar et al (2019) that reported higher age range of the selected subjects. The most affected age group in this study was 6-11years.…”
Section: Discussionsupporting
confidence: 90%
“…Main points regarding acute abdomen should include pain location, radiation, intensity and nature of pain, previous episodes of acute abdomen, and the intensity or progression of the pain, as well as associated symptoms (Hijaz and Friesen, 2017). Kumar et al (2019) reported that the gaps between the acute abdominal pain and acute abdomen overlap and are used interchangeably in clinical practice.…”
Section: Introductionmentioning
confidence: 99%